Construction and validation of a questionnaire for determining the individual trajectory of personal and intellectual development of a schoolchild - MALYSHEVA, Karine; LYTVYN, Sergiy; MAKSYMCHUK, Mariia; KELLER, Vladyslava (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2025)
Background. This article describes the procedure for constructing and evaluating the psychometric properties of a questionnaire designed to determine the individual trajectory of a schoolchild’s personal and intellectual development. The questionnaire assesses the following parameters: intellectual values and need for cognition, managerial and everyday life skills, as well as communication skills and assertiveness—factors that influence students’ self-efficacy and well-being in the educational environment. Two equivalent versions of the questionnaire were developed, each comprising 73 items distributed across five scales. Methods. The validation of the questionnaire for determining the individual trajectory of personal and intellectual development was conducted on a sample of 127 students from grades 5 to 11 of general secondary education institutions. Additionally, 35 parents participated in the study. For validation purposes, the following tests were employed: the "Need for Cognition Scale", the "Adolescent Assertiveness Scale", and the "Executive Functions Questionnaire". Results. The overall Cronbach’s Alpha for version A of the questionnaire is 0.873, and for version B it is 0.879, indicating high internal consistency and reliability of both versions. A strong, statistically significant correlation (p ≤ 0.001) between the scales of versions A and B allows them to be used as equivalent forms. Criterion validity is confirmed by high correlations between student and parent responses on the scales "Time Management and Executive Functions" (r = 0.725), "Everyday Life Skills" (r = 0.686), and "Socialization Skills" (r = 0.616). Concurrent validity is supported by the close correlation between the scale "Need for Cognition, Anti-Intellectualism, and Reading Barriers" and the standardized "Need for Cognition" test (r = 0.735), as well as between the developed "Assertiveness" scale and the validated "Adolescent Assertiveness Scale" (r = 0.389). Conclusions. The psychometric indicators of internal consistency, reliability, and validity are statistically significant, supporting the use of the developed questionnaire in educational settings.